A Framework for Collective Robot Control: Integrating Crowd-Choice Mechanisms with DAO Governance - Duguleană Mihai; Duguleană Andreea Raluca; Tănăsescu Cristina Roxana; Gîrbacia Florin (My University, 2025)
In the contemporary robotics landscape, decentralized governance mechanisms offer promising avenues for democratizing control over robotic activities. This paper introduces a new framework integrating crowd-choice mechanisms inspired by Decentralized Autonomous Organizations (DAOs) with robotic control systems. Our framework enables any stakeholder (individuals, companies, public institutions, NGOs and so on) to collectively determine robot activities through transparent and auditable decision-making processes. By leveraging blockchain technology, users can participate in prioritizing and executing robot actions, similar to DAO voting. We outline the architecture, implementation guidelines, and potential applications of the framework across diverse domains such as industrial automation, healthcare, and disaster response. Furthermore, we discuss the governance model, security considerations, and future research directions in advancing decentralized robotics governance. Through this framework, we envision a paradigm shift towards inclusive, transparent, and efficient multi-user robot control.